PENINGKATAN KETERAMPILAN KOMUNIKASI EFEKTIF MELALUI PELATIHAN DI LINGKUNGAN KERJA KULINER THE GREENBRIER RESORT, AMERIKA SERIKAT - Adrina, Ni Putu Irmanita; Susanti, Luh Eka; Arianty, Anak Agung Ayu Arun Suwi; Sari, Retno Juwita (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Community service activities were carried out in the kitchen environment of The Greenbrier Resort, United State. This activity included improving the effective communication skills of kitchen staff. There were communication barriers that occurred between senior and junior staff and coordination barriers with the food service department that affected work efficiency. A series of activities were carried out to overcome these barriers, including field observations, informal interviews, and training based on work situation simulations. Training in strengthening listening skills, feedback, and empathetic two way communication proved beneficial because the results showed increased self confidence among junior staff and the creation of a more open and collaborative work climate. The activity demonstrated how participatory training in real work conditions can improve communication effectiveness in a professional kitchen.